Analisis Konsep Demokrasi Semu dalam OSIS : Tinjauan Pendidikan Kewarganegaraan - Ali Wafa Rabbani; Kokom Komalasari; Nisrina Nurul Insani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The concept of selecting the student council president in schools that implements democratic values ​​is still often found to be misunderstood in practice. The continuity of the student council president election which should be carried out freely, honestly, and fairly but often there are still influences from irresponsible parties. Democratic values ​​that should uphold the rights of every human being are tarnished by dirty practices that often occur in the election of the student council president in schools. This study uses a research method with data collection through library studies from various literature such as articles, websites, the internet, news and others that are credible and trusted.